Jejak langkah fiqh: studi kronologis perkembangan hukum islam dari masa rasulullah hingga kontemporer - nugroho, Teguh Agung (Maliki Interdisciplinary Journal, 2025)
This study aims to trace the historical trajectory of the development of Fiqh (Islamic jurisprudence) chronologically, from its foundational period during the time of the Prophet Muhammad (PBUH) to its dynamics in the contemporary era. The research employs a historical-analytical approach to analyze the transformation of methodologies, sources, and characteristics of Fiqh in each historical phase. The findings indicate that Fiqh has undergone dynamic and multi-layered evolution. It began with the Formation phase during the Prophet’s era, which was directly derived from divine revelation, then moved into the Foundation and Consolidation phases during the era of the Rightly Guided Caliphs and the Codification period, where the various schools of jurisprudence emerged and flourished. The subsequent phase of Stagnation (Taqlid) also shaped the character of Islamic law before it was revitalized through the Revival (Tajdid) movement and faced new challenges in the Contemporary era. The conclusion of this study affirms that understanding this chronology of Fiqh’s development is crucial for addressing modern legal issues while adhering to the fundamental principles of Sharia, thereby demonstrating the flexibility and enduring relevance of Fiqh throughout history.